The clinical and genetic spectrum of primary familial brain calcification - Carecchio, Miryam; Mainardi, Michele; Bonato, Giulia (Journal of neurology, 2023)
Primary familial brain calcification (PFBC), formerly known as Fahr’s disease, is a rare neurodegenerative disease characterized by bilateral progressive calcification of the microvessels of the basal ganglia and other cerebral and cerebellar structures. PFBC is thought to be due to an altered function of the Neurovascular Unit (NVU), where abnormal calcium-phosphorus metabolism, functional and microanatomical alterations of pericytes and mitochondrial alterations cause a dysfunction of the blood–brain barrier (BBB) and the generation of an osteogenic environment with surrounding astrocyte activation and progressive neurodegeneration. Seven causative genes have been discovered so far, of which four with dominant ( SLC20A2 , PDGFB , PDGFRB , XPR1 ) and three with recessive inheritance ( MYORG , JAM2 , CMPK2 ). Clinical presentation ranges from asymptomatic subjects to movement disorders, cognitive decline and psychiatric disturbances alone or in various combinations. Radiological patterns of calcium deposition are similar in all known genetic forms, but central pontine calcification and cerebellar atrophy are highly suggestive of MYORG mutations and extensive cortical calcification has been associated with JAM2 mutations. Currently, no disease-modifying drugs or calcium-chelating agents are available and only symptomatic treatments can be offered.